Subfatin concentration decreases in acute coronary syndrome - Yilmaz, Mustafa; Goktekin, Mehmet Cagri; Ilhan, Nevin (Croatian Soc Medical Biochemistry & Laboratory Medicine, 2022)
Introduction: We investigated the association of serum subfatin concentration and acute myocardial infarction (AMI) in patients with ST-elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI). Materials and methods: In this study, patients who presented with chest pain (STEMI, NSTEMI, or non-cardiac chest pain) were included, i.e. 49 patients with non-cardiac hest pain (control) and 66 patients hospitalised with AMI. In the AMI group, 35 patients had NSTEMI and 31 had STEMI. Serum subfatin concentrations were determined via enzyme-linked immunosorbent assay (ELISA). Descriptive data on the patients and their comorbidities were recorded, and subfatin concentrations were analysed. Results: Subfatin concentrations were significantly different in the control, STEMI and NSTEMI groups (P = 0.002). In addition, subfatin concentrations were significantly lower in patients in the NSTEMI group than those in the control group (P < 0.001), but there was no significant difference between STEMI and the control group (P = 0.143). The receiver operating characteristic (ROC) analysis performed for differentiating the AMI and control groups found that subfatin had 64% sensitivity and 69% specificity, whereas troponin had 59% sensitivity and 95% specificity. In patients with AMI, the ROC analysis for differentiating NSTEMI from STEMI found that subfatin had 94% sensitivity and 41% specificity, while troponin had 65% sensitivity and 88% specificity. Conclusions: Subfatin concentrations were lower in patients without STEMI than in patients with STEMI. Subfatin concentration is associated with NSTEMI.
Keywords: acute coronary syndrome; acute myocardial infarction; non-ST-elevation myocardial infarction (NSTEMI); ST-elevation myocardial infarction (STEMI); subfatin